Frecuencia de hábitos orales en escolares de 5 a 14 años en la ciudad de Santiago de Cali - Hernández Silva , Jesús Alberto; Soto Llanos, Libia; Villavicencio Florez, Judy (Revista Estomatología, 2002)
A descriptive study was made at the Rufino José Cuervo educative center, with 173 children 5 to 14 year old. These children were orally healthy, it means out of cavities, periodontitis and lost temporal or permanent teeth. Ninety children (52%) had at least one kind of habit, some cases presented two kinds of habits. Habits delected were digital suction, 23 cases (25.5%), onicophagia 50 cases (55.5%), atypical deglution in 14 cases (15.5%), tongue habit 8 cases (8. 9%) objects in mouth in 6 cases (6.6%), mouth breath in 2 cases (2.2%), inferior lip in one cases (1.1%) and bottle use in one (1.1%).